PowerPlex® fusion 6C system: internal validation study - Ana Boavida; Vanessa Bogas; Lisa Sampaio; Nair Gouveia; Maria J. Porto; Francisco Corte-Real (Oxford University Press, 2018)
This work is aimed at describing the proceedings and parameters used to validate PowerPlex® Fusion 6C System, the polymerase chain reaction (PCR) amplification kit by Promega, for posterior implementation in the laboratorial routine of the Forensic Genetic Service. The PowerPlex® Fusion 6C System allows multiplex PCR, through simultaneous amplification and posterior detection by fluorescence of 27 loci. Characterization of the kit was made according to the laboratory's internal validation procedure based on validation guidelines from Scientific Working Group on DNA Analysis Methods. Some parameters were evaluated, such as specificity, analytical thresholds, sensitivity, precision, mixture studies, DNA control samples, a proficiency test and changes in the PCR-based procedures: final reaction volume and cycle number, changes in the reaction mixture for direct amplification. This kit proved to be very robust and the results are in concordance with previous developmental validation by the manufacturer. In some parameters, the results were better than expected.